PENINGKATAN KEDISIPLINAN ANAK DENGAN POLA ASUH YANG TEPAT MENURUT IBRANI 12:5-11 - Panjaitan, Firman (Shift Key : Jurnal Teologi dan Pelayanan, 2022)
This study discusses parental education in disciplining children in Hebrews 12:5-11. There are errors in parenting patterns in disciplining children, causing acts of violence in the family, and this has a bad impact on children which is reflected in bad and difficult child behavior. Parents must understand the how to discipline their children properly and correctly based on the truth of God's Word. This study uses a qualitative method, especially a literature study approach, which is to collect data for analysis and is assisted by exposition approach to find the meaning in Hebrews 12:5-11. The results of the study revealed that the act of educating children is evidence of parental love, so parents must warn their children. If in disciplining children, there is an action to punish the child, then it is intended to bring good to the child; thus discipline is not to hurt but to give peace. The concept of education in the form of discipline, punishment, and instruction is aimed at shaping children's character for the better. Thus, the purpose of this study is to find the best way to discipline children, especially through the study of the interpretation of Hebrews 12:5-11.